Assessing Singapore's Role and Impact in SIDS Framework Case Study: Implementation The SAMOA Pathway - Anaaisyah, Risqi; Radhana, Javiar Duvadilan; Al Anwary, Muhammad Hanan Amin; Hidayatullah, M. Bintang; Aryokusumo, Brilliando Lintang (Journal of International Relations on Energy Affairs, 2023)
This research will evaluate Singapore's strategic role in supporting the implementation of the SAMOA Pathway framework for Small Island Developing States (SIDS), with a focus on the renewable energy agenda through the "SIDS of Change" initiative. The SAMOA Pathway framework, launched in 2014, aims to promote environmental sustainability, social inclusion, and economic resilience for small island nations. This study applies Robert Keohane's Liberal Institutionalism theory, which emphasizes the importance of multilateral cooperation and the role of international institutions in facilitating collaboration among nations to address collective challenges.The research adopts a qualitative method with a descriptive analytical approach. Primary data is obtained through interviews with experts in the fields of energy and sustainable development, while secondary data is collected from academic journals, official reports, and related policy documents. To enhance validity, the study employs data triangulation to compare information from various sources. The findings indicate that Singapore plays a crucial role in supporting SIDS through capacity-building programs such as the Singapore Cooperation Program (SCP), which facilitates technology transfer and foreign direct investment (FDI). Singapore leverages its strengths in renewable energy technologies, such as Carbon Capture and Storage (CCS) development and solar farm projects, to build strategic partnerships with SIDS. However, challenges such as the bureaucratic complexities among SIDS and the lack of immediate economic benefits for Singapore hinder the implementation of this agenda. From the perspective of Liberal Institutionalism, Singapore's contributions highlight the importance of international institutions in creating opportunities for countries with similar challenges to collaborate.